لوْحَة السَّيْل في الشعْر الجاهِليّ Scenery of Torrent in (pre-Islamic) JÉhilÊ Arabic Poetry - (Saleh Taha Ajluni (Saleh Taha Ajluni), صالح طه العجلوني (At-Tajdid - Intellectual Refereed Journal, 2014)
للماء في حياة الكائنات الحية أهمية كبرى؛ إذ لا يمكنها البقاء على قيد الحياة من دونه، وله في حياة البشر الأهمية ذاتها بل أهمية أكبر، فهم لا يستغنون عنه في مختلف شؤونهم، فهو منبع الحياة كما جاء في القرآن الكريم: ﴿ ﮞ ﮟ ﮠ ﮡ ﮢ ﮣ ﴾ (الأنبياء: 30). والعرب - الذين شاء لهم قدرهم أن يعيشوا في بيئة صحراوية قاحلة - ربما كانوا أشد الناس إدراكًا لأهمية هذا العنصر الحيوي في بقائهم، ولذلك أحاطوه بكثير من العناية، وأولوه جانبا كبيرًا من اهتمامهم، بل إن كثيرًا من حروبهم وأيامهم كانت تقع بسبب التنازع على امتلاك مصادر المياه، أو حتى على أولوية ورودها والانتفاع بها. إلا أنه في مقابل هذه الصبغة الإيجابية للماء من حيث هو مصدر للحياة، قد يكتسي هذا العنصر صبغة أخرى مناقضة حين يتحول إلى عنصر دمار وخراب وإفناء، وذلك حين ينهمر المطر بغزارة، ويغرق ماؤه السهول والهضاب والجبال؛ فتنحدر تلك المياه مشكّلة سيولاً جارفة تأخذ في طريقها كلّ ما يصادفها من أوجه الحياة، فتحيل الديار العامرة إلى خراب، وتقتلع الأشجار، وتقتل البشر والحيوان. وقد اهتمّ الشعراء الجاهليون بالحديث عن تلك الصورة التي تمثلها قوة الدمار في الماء، وأعني بها قوة السيل، فحفلت كثير من قصائدهم بتصوير مشهد السيل، وبيان الآثار التي يتركها في الأرض، وما عليها من نبات، وحيوان، وبشر. ونقف في هذا البحث عند مشاهد هذا الجانب التدميري للماء؛ لنرصد صوره وتجلياته كما التقطها، وسجلها عدد من الشعراء الجاهليين، كما نستعرض أهمّ ما كتبه النقاد العرب حول مشهد السيل وأثره في تحديد البنية العامة للقصيدة الجاهلية. الكلمات الأساسية: الشعر الجاهلي، الشعراء الجاهليون، الماء، السيل، الدمار، النقاد العرب، بنية القصيدة. _________________________________________________ Water is so important in the lives of living beings, as none of them can survive without it. It has the same, nay a greater, importance for human beings, for they cannot do without it in all aspects of their existence. Water is in fact the source of life as stated by the Qur’an: “We made out of water every living thing” (Qur’an, 21: 30). The Arabs whose destiny has been to live in an arid desert environment might be more disposed to realize the significance of this vital element for their survival. Hence, they attached much attention and concern to it; indeed many of their wars and great events occurred due to conflict over controlling water sources or even over the priority of access to and use thereof. However, in opposition to this positive characteristic of water as a life-giving source, this element may have a different characteristic as it turns into a factor of destruction, ruin and extinction. This happens when heavy rains inundate plains and hills as well as mountains and give rise to torrential floods, thus sweeping away all aspects of life in their way and leaving behind ruin and devastation, by uprooting trees, demolishing houses and killing animals and human beings. Pre-Islamic JÉhilÊ Arab poets paid much attention to this destructive aspect of water, especially the torrential floods. Many of their poems are replete with descriptions of the torrent and its devastating effects on the land and all that is on it, including plants, animals and people. In this article we examine this destructive aspect of water and its manifestations as recorded and portrayed by a number of Pre-Islamic JÉhilÊ poets. We also discuss what Arab literary critics have to say on the scenery of torrents and its effect in terms of shaping the overall structure of the pre-Islamic JÉhilÊ qaÎÊdah. Key words: Pre-Islamic JÉhilÊ Arabic Poetry, pre-Islamic JÉhilÊ poets, water, torrential flood, destruction, Arab literary critics, structure of the qaÎÊdah.